Restructuring shipbuilding enterprises as the basis of its economic growth - Єфімова, Г. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
One of the major factors of economic development of shipbuilding companies are their system restructuring. The study aims to define the content and methodology of the restructuring of shipyards using theoretical synthesis and system analysis of modern approaches to its implementation. The restructuring of shipyards is the process of complex change of financial and economic, technological, manufacturing and marketing, organizational and management structure of the company and methods of operation. This will ensure effective use of the potential of the company and maximize its value. The tools of solution in the process of restructuring of the main problems of shipyards were identified On the basis of their systematization. Types of restructuring and the corresponding possible reasons and changes in the company were identified by the functional areas of business. The restructuring of shipyards is a complex process of structural transformation and innovation. It aims to ensure sustainable, efficient development of enterprise and increasing business value in terms of external and internal environment dynamically changes. Regardless of the approach to the restructuring of shipyards, its necessary correctly identify its conception, principles of the transformation implementation and estimation method of the final result of planned changes.